Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

9x-8y=4
2x-3y=-4
Solving for elimination


Sagot :

Use simultaneous equations;

9x - 8y = 4

2x - 3y = -4

We can rearrange the second one to say that:

2x = 3y - 4

x = [tex] \frac{3y-4}{2} [/tex]

so;

9([tex] \frac{3y-4}{2} [/tex]) - 8y = 4

9(3y - 4) - 16y = 8

27y - 36 - 16y = 8

11y = 44

y = 4

We then substitute y = 4 back into an original equation

9x - 8y = 4

9x - 8*4 = 4

9x - 32 = 4

9x = 36

x = 4

Final answer;

x = 4, y = 4

you could multiply the top equation by 3 and the bottom by -6 so then it would be:
27x-24y=12
-12x+24y=24
you can then get rid of the y since they cancel out each other, so you end up with:
27x=12
-12x=24
combine these two equations so you get:
15x=36
divide both sides by 15 so you get:
x=2.4
then plug x into one of the equations to find y:
2.4-3y=-4
subtract 2.4 from each side
-3y=-6.4
divide both by -3:
y=-2.13
so y=-2.13 and x=2.4